Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1136/jclinpath-2016-203821
|View full text |Cite
|
Sign up to set email alerts
|

Single thyroid tumour showing multiple differentiated morphological patterns and intramorphological molecular genetic heterogeneity

Abstract: Although all of the morphological patterns in this tumour have been reported as having aetiological or other association with one another, there was only partial concordance with their molecular signatures. There was significant molecular discordance, however, even with identical morphologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 14 publications
3
12
0
Order By: Relevance
“…Similar conclusions were made in the report on a case with simultaneous independent papillary and medullary carcinomas [24]. Moreover, distinct morphological components of a composite thyroid carcinoma also had highly different mutational profiles, indicating divergent growth and no clonal association despite the close spatial relationship [28].…”
Section: Discussionsupporting
confidence: 87%
“…Similar conclusions were made in the report on a case with simultaneous independent papillary and medullary carcinomas [24]. Moreover, distinct morphological components of a composite thyroid carcinoma also had highly different mutational profiles, indicating divergent growth and no clonal association despite the close spatial relationship [28].…”
Section: Discussionsupporting
confidence: 87%
“…These discrepancies may be due to the large number of patients in our cohort who had PTC components, as characterised by the presence of BRAF mutations . Because tumour histology can greatly affect intratumour molecular heterogeneity, it is imperative to sample multiple tumour sites for mutational profiling to obtain a conclusive and comprehensive genetic landscape of the tumour …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, such heterogeneity detected at the microscopic level does not necessarily reflect the degree of heterogeneity present at the molecular level. Indeed, several studies have confirmed the high intratumour variation in the PTC dissimilarity of each single tumour [25, 26]. …”
Section: Phenotypic and Molecular Heterogeneity Of Tc Subtypesmentioning
confidence: 99%
“…The possible explanations for this variation proposed by the authors included a multiclonal origin of the tumour and that RET rearrangements may constitute a later subclonal event. An interesting case was reported by Schopper et al [26], who analysed a single thyroid tumour that showed a combination of conventional PTC, the follicular variant of PTC, clear-cell PTC, columnar-cell carcinoma, and PDTC. The authors used massively parallel next-generation sequencing (NGS) using a laboratory-developed NGS panel of 8 cancer-related genes ( BRAF , KRAS , HRAS , NRAS , EGFR , PIK3CA , KIT, and PDGFRA ) to analyse each morphological component and metastasis.…”
Section: Phenotypic and Molecular Heterogeneity Of Tc Subtypesmentioning
confidence: 99%